Evidence for possible association of vitamin D status with cytokine storm and unregulated inflammation in COVID-19 patients - Daneshkhah, Ali; Agrawal, Vasundhara; Eshein, Adam; Subramanian, Hariharan; Roy, Hemant Kumar; Backman, Vadim (Aging clinical and experimental research, 2020)
Objectives We present evidence for a possible role of Vitamin D (VitD) deficiency in unregulated cytokine production and inflammation leading to complications in COVID-19 patients. Design The time-adjusted case mortality ratio (T-CMR) was estimated as the ratio of deceased patients on day N to the confirmed cases on day N-8. The adaptive average of T-CMR (A-CMR) was calculated as a metric of COVID-19 associated mortality. A model based on positivity change (PC) and an estimated prevalence of COVID-19 was used to determine countries with similar screening strategies. A possible association of A-CMR with the mean concentration of 25-hydroxyvitamin D (25(OH)D) in elderly individuals in countries with similar screening strategy was investigated. We considered high C-reactive protein (CRP) in severe COVID-19 patients (CRP ≥ 1 mg/dL) as a surrogate of a cytokine storm. We considered high-sensitivity CRP (hs-CRP) in healthy subjects as hs-CRP ≥ 0.2 mg/dL. Results A link between 25(OH)D and A-CMR in countries with similar screening strategy is evidence for VitD’s possible role in reducing unregulated cytokine production and inflammation among patients with severe COVID-19. We observed an odds ratio (OR) of 1.8 with 95% confidence interval (95% CI) (1.2 to 2.6) and an OR of 1.9 with 95% CI (1.4 to 2.7) for hs-CRP in VitD deficient elderly from low-income families and high-income families, respectively. COVID-19 patient-level data show an OR of 3.4 with 95% CI (2.15 to 5.4) for high CRP in severe COVID-19 patients. Conclusion We conclude that future studies on VitD’s role in reducing cytokine storm and COVID-19 mortality are warranted.